Anti-Inflammatory, Antioxidant, and Healing-Promoting Effects of Aloe vera Extract in the Experimental Colitis in Rats. (6th December 2021) - Naini, Mahvash Alizade; Zargari-Samadnejad, Asal; Mehrvarz, Shayan; Tanideh, Romina; Ghorbani, Mohammad; Dehghanian, Amirreza; Hasanzarrini, Maryam; Banaee, Farnaz; Koohi-Hosseinabadi, Omid; Tanideh, Nader; Iraji, Aida
Abstract : Background . Ulcerative colitis is a worldwide chronic gastrointestinal disease characterized by variable extensions of colon mucosal inflammation. The available drugs have an incomplete response with various side effects and socioeconomic impacts. Aloe barbadensis Miller (Aloe vera) is a well-known medicinal plant with diverse pharmacological and therapeutic activities. As a result, in the current study, Aloe vera was selected to evaluate its therapeutic effects on experimental colitis in rats. Methods . This study is intended to evaluate the possible beneficial effect of Aloe vera for the treatment of experimental colitis. Trinitrobenzenesulfonic acid (TNBS) was used to induce experimental colitis in 60 of 70 Wistar rats. The rats were grouped in 7 clusters including healthy control, negative, positive control (received sulfasalazine), and test groups treated with Aloe vera extracts via oral or rectal routes. Macroscopic and histologic factors as well as the biochemical parameters were evaluated on day 7. Results . In the present study, it was found that serum levels of tumor necrosis factor- α (75 vs. 44 pg./ml), interleukin-6 (41 vs. 21 pg/ml), and nitric oxide (24 vs. 6 μ m/ml) in TNBS-induced untreated colitis treatment were significantly increased as compared to healthy control. Similar patterns were also observed in malondialdehyde (76.41 vs. 236.35 μ g/mg) and myeloperoxidase (4.24 vs. 29.38 U/mg) in colonic tissue. Among different treatments, rectal administration of Aloe vera extract (400 mg/kg) exhibited the best result in which serum concentration of tumor necrosis factor- α (55 pg/ml), interleukin-6 (24 pg/ml), and nitric oxide (10 μ m/ml) and the levels of malondialdehyde (102.67 μ g/mg), as well as myeloperoxidase (12.29 U/mg) in colon tissue, were reduced as compared to the untreated group. Also, the body weight and colon weight/length ratios were more improved in the treated group with 400 mg/kg Aloe vera extract, rectally. Conclusion . Aloe vera extract exhibited a therapeutic effect in TNBS-induced colitis, and local, rectal administration of Aloe vera extract was more effective than oral administration.